The effects of psychological safety and employee voice behavior on flight attendants’ mindful safety practices adoption - Hu, Shi; Nadeem, Muhammad Aamir; Luo, Ji; Yi, Xiaobo (Frontiers in Public Health, 2024)
Introduction Flight attendants, as the front-line staff in the cabin, play a crucial role in improving air travel safety. This research explores how psychological safety affects flight attendants’ adoption of mindful safety practices through voice participation. This mechanism also identifies ethical leadership and traditionality as two moderators. Methods A self-reported questionnaire was used to collect data from 621 flight attendants in Chinese private commercial airline companies. PLS-SEM (partial least square structured equation modeling) is used to examine the hypotheses proposed in the present study. Results After data analysis, the results reveal that the underlying mechanism covering both mediating and moderating effects through which flight attendants’ voluntary and extra-role safety behavior could be improved. Discussion The findings extend the existing literature regarding the antecedents of flight attendants’ mindful safety practices adoption and obstacles to employee voice participation. Managerial implications are also provided in the commercial aviation industry and discussed along with future research directions.